2023
DOI: 10.1007/s42765-023-00297-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Superhydrophobic and Antibacterial Cellulose-Based Fibers and Fabrics: Bio-inspiration, Strategies, and Applications

Abstract: Cellulose-based fabrics are ubiquitous in our daily lives. They are the preferred choice for bedding materials, active sportswear, and next-to-skin apparels. However, the hydrophilic and polysaccharide characteristics of cellulose materials make them vulnerable to bacterial attack and pathogen infection. The design of antibacterial cellulose fabrics has been a long-term and on-going effort. Fabrication strategies based on the construction of surface micro-/nanostructure, chemical modification, and the applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 255 publications
0
3
0
Order By: Relevance
“…This journal is © The Royal Society of Chemistry 2024 the hydrophobicity and hydrophilicity of the implant surface is a good way to hinder bacterial adhesion. 101 Because of the hydrophobicity of the surface, the presence of an air layer between materials and liquid can reduce the bacterial adhesion sites and thus reduce bacterial adhesion (Fig. 3(C1) and C2)).…”
Section: Surface Micro-nano Structurementioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2024 the hydrophobicity and hydrophilicity of the implant surface is a good way to hinder bacterial adhesion. 101 Because of the hydrophobicity of the surface, the presence of an air layer between materials and liquid can reduce the bacterial adhesion sites and thus reduce bacterial adhesion (Fig. 3(C1) and C2)).…”
Section: Surface Micro-nano Structurementioning
confidence: 99%
“…using graft polymerization, the plasma method, and sol-gel. Cellulose-based materials are the favored choice for bedding, sportswear, and intimate apparel thanks to their manifold benefits [55]. Liu et al [56] reported a facile one-step process to convert the completely hydrophilic cellulose non-woven substrate into highly hydrophobic fabrics (water contact angle of 130 • -135 • ) through the preservation of good air permeability (variation ± 6% after modification compared to the original 1337 mm.s −1 ) (Figure 4c).…”
Section: Cellulose-based Superhydrophobic Textilesmentioning
confidence: 99%
“…Antibiofouling surfaces prevent the proliferation of bacteria, decreasing the availability of initial attachment of bacteria, while bactericidal surfaces directly kill bacteria [46]. The anti-biofouling property refers to a surface that can impede the growth and reproduction of bacteria by affecting the bacterial metabolic processes, disrupting cell wall formation, or even perturbing essential functions of certain cells [47][48][49]. Hence, the antibacterial principle is to avoid bacteria proliferating and decreasing biofilm formation by eliminating essential nutrient sources to the correct bacteria growth or adding elements that could affect the bacteria biofilm formation [47,50].…”
Section: Antibiofouling and Bactericide Propertiesmentioning
confidence: 99%
“…In their initial stages, designs for bactericidal surfaces predominantly relied on chemical methods as standalone approaches. These methods involved incorporating silver nanoparticles or applying antimicrobial compounds to the surface, effectively achieving their intended antibacterial effect [6,49]. While these strategies have demonstrated success, they have also introduced certain challenges, like environmental concerns related to toxicity, as well as the gradual decrease in effectiveness over time due to the bacterial resistance and possible degradation and diminishing concentration of the active compounds [7,65].…”
Section: Antibiofouling and Bactericide Propertiesmentioning
confidence: 99%